Fieldwork as a strategy for theoretical and practical integration. An interdisciplinary work experience (Huellas, 2025)
Geography has continuously updated its concepts and methodologies in alignment with the epistemological approaches that have consolidated throughout its disciplinary history. In this process, concepts such as geographic space, landscape, region, place, and territory have acquired new meanings and analytical perspectives, enabling a more complex and critical view. In the fields of teaching and research, there is a growing need to incorporate methodologies that contribute to the construction of knowledge through observation and concrete, situated experience. The purpose of this paper is to present a teaching-learning experience carried out in the subject "Introduction to Geography," part of the Geography and History programs at the Universidad Nacional del Sur. This fieldwork activity was proposed to students through a tour around some areas in the city of Bahía Blanca. The preparation for this project takes place throughout the duration of the subject, allowing for the co-construction of meaningful knowledge about the space, which enables students to critically engage with and question the observed reality. The experience is offered as an enriching proposal for spatial learning, an opportunity for interdisciplinary dialogue, and a catalyst for the development of critical research proposals.